2005
DOI: 10.1002/arch.20042
|View full text |Cite
|
Sign up to set email alerts
|

Biorational insecticides: Mechanism and cross‐resistance

Abstract: Potency and cross-resistance of various biorational insecticides, exemplified by the whitefly Bemisia tabaci, have been studied. Bemisia tabaci were exposed to the juvenile hormone mimic pyriproxyfen for the past 12 years resulting in an over 2,000-fold resistance, but there was no appreciable cross-resistance with the benzoylphenyl urea novaluron. Similarly, no cross-resistance was found between pyriproxyfen and the two neonicotinoids, acetamiprid and imidacloprid. On the other hand, a slight cross-resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 30 publications
0
26
1
1
Order By: Relevance
“…This hormone plays a crucial role in insect development, and it is theorised that its agonists or antagonists may disrupt the physiological processes of the target pest (Oberlander & Smagghe 2001, Yanagi et al 2006. Over the past four decades, efforts have been made to develop insecticides with selective properties that act speci ically on biochemical sites that are present in particular insect groups but with properties that differ from other insecticides (Ishaaya et al 2005). This approach has led to the discovery of today's modern insect growth regulator (IGR) insecticides (Dhadialla et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This hormone plays a crucial role in insect development, and it is theorised that its agonists or antagonists may disrupt the physiological processes of the target pest (Oberlander & Smagghe 2001, Yanagi et al 2006. Over the past four decades, efforts have been made to develop insecticides with selective properties that act speci ically on biochemical sites that are present in particular insect groups but with properties that differ from other insecticides (Ishaaya et al 2005). This approach has led to the discovery of today's modern insect growth regulator (IGR) insecticides (Dhadialla et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It was assessed as highly effective against mosquito larvae and pupae (particularly Aedes aegypti but also Anopheles, Culex and C. Quinquefasciatus) at low dosage (1-5 µg/liter AI). Novaluron has no crossresistance with other leading compounds for controlling whiteflies such as buprofezin, pyriproxyfen, acetamiprid or imidacloprid (Ishaaya et al 2005). In a study on its effect on silverleaf whitefly reproduction, it was concluded that novaluron negatively affects female reproduction by reducing egg viability-an important long-term pest-management strategy that may reduce the number of insecticide applications (Cloyd et al 2004).…”
Section: Novaluron: a Novel Igrmentioning
confidence: 97%
“…But these chemicals with varied mode of action due to indiscriminate use carry the danger of resistance development, pest resurgence, outbreaks of secondary pests, and reduction in biodiversity of natural enemies, and bioconcentrations of residues in consumable produce at harvest (Mitra et al, 1999;Krishnamurthi, 1999;Agnihotri, 1999). These considerations have led to the development of newer insecticide molecules with novel mode of action and with least residue effects on consumables and environment (Ishaaya et al, 2005;Moosa Saber et al, 2013). Biorational insecticides like insect growth regulators are the prospective option in IPM of crop pests in recent times.…”
Section: Introductionmentioning
confidence: 99%